USE OF INFUSED WATER HEALTHY DRINKS AS BODY RESISTANCE WITH PKK MANAGERS OF BANGAK SINE VILLAGE SRAGEN - Kurniawan Kurniawan; Nurul Marfu'ah; Fauziyyah Al Hasanah; Muthi’ah Rabbaniyah; Satwika Budi Sawitri (PC IAI Sragen, 2023)
The use of infused water as a healthy drink for endurance needs to be widely disseminated in society after the Covid 19 pandemic. Infused water or spa water is water that is added with pieces of fruit and left for a few hours until the juice comes out, then it is ready to be consumed, thus giving the impression taste and health benefits. Infused water can be used as an alternative for those who don't or don't like fruit and don't have time to consume fruit. The purpose of this community service program is to increase the skills and knowledge of the community in making infused water, as well as the importance of increasing the body's immunity by utilizing health drinks such as infused water. The method used is descriptive, lecture, discussion and hands-on practice of making infused water with PKK administrators in Bangak Sine village, Sragen Regency. The results of this community service activity can be seen from the increased knowledge and ability of the participants in making the correct infused water according to the instructions previously socialized. The conclusion of this community service activity is that participants can make infused water independently and increase public knowledge about the benefits of infused water as an immune booster